Determination of selected heavy metals by stable isotope approach of food web assemblage in intertidal mangrove ecosystem, Sungai Puloh, Selangor, Malaysia - Emeka, Udechukwu Bede (2016)
The mangroves of Sungai Puloh which supports a great diversity of macro benthic organism and provides social benefits to the local community is becoming a major recipient of the anthropogenic contaminants as a result of industrialization, expansion of population, and urbanization. This study was conducted to evaluate the concentrations, contamination extent, distribution and mobility, and pollution status of heavy metals (Cd, Cu, Ni, Pb, Zn and Fe) in intertidal surface sediment of this mangrove area. The speciation profile of these heavy metals as well as the sediment total organic carbon (TOC) and pH were also determined. This work also elucidated the heavy metal levels in the food web structure and trophic dynamics of macrobenthic organisms in this area. Forty two surface sediment samples were collected from 14 stations representing 4 group sites of possible different anthropogenic sources, and selected macro fauna were randomly collected. The four stage sequential extraction technique (SET) was employed to investigate the heavy metal distribution pattern, while the Risk assessment Criteria Code (RAC) was applied to estimate the metals bioavailability and implication to food chain. And the stable isotope ratio technique was used to determine the trophic positions, dynamics and material flow. The heavy metals concentrations were analyzed using atomic absorption spectrophotometer and the result were presented in μg/g, except for Fe in %. Interim Sediment Quality Guidelines (ISQG) and different contamination indices were employed to determine the quality of surface sediment. The mean values of analyzed metals were below both the ISQG-low and ISQG-high except for Pb concentration that is above ISQG-low, and Zn concentration which is above ISQG-high suggesting Pb and Zn may pose some environmental concern. Pollution Load Index (PLI) indicated deterioration and other indices revealed that the surface sediment is moderately polluted with Cd, Pb, and Zn. Chemical speciation depicted the non-residual fractions of Cd 53%, Ni 51%, and Pb 43.91% to be at the borderline for remobilization. Based on the RAC, Pb and Ni in Sg. Puloh ecosystem pose low risk, while Cd and Zn showed a higher risk to enter into the food chain. The findings of high Pb concentrations in fiddler crabs which are ubiquitous in this study area, and the elevated levels of Pb in catfish which is commercial seafood and a good source of protein to the local community makes Pb the most incriminating contaminant in the study area. With the help of stable isotope ratios of δ13C and δ15N analysis, two distinct food chains and four trophic positions were determined, with catfish occupying the highest trophic level. By using catfish as a model for trophic web system, stable isotope analysis showed that the carbon source for catfish is discretely from fiddler crabs, complementing the idea that uca annulipes found in the stomach content is its staple food. Generally, we concluded that increased anthropogenic activities through industrialization and urbanization impact, and as well lead to heavy metal contamination in Sungai Puloh mangrove estuary through the release of untreated or poorly/ improperly treated effluents. And these heavy metals contamination are evidenced in the food web of Sg. Puloh mangrove. However, the seafood in Sg. Puloh is considered safe for human consumption yet, Pb is considered to be the element of much concern, and therefore should be strictly monitored.